The use of a cell phone application to access the nursing protocol: an experience report (Research, Society and Development, 2020)
This report aims to socialize the experience of a group of nurses with the creation and use of an application to standardize the standard operating protocols for nursing care, built using a free platform and a self-explanatory tool. This is an account of the experience of a group of nurses, in a public health institution of urgency and emergency, in the State of Rio de Janeiro, from January to March 2020. It is known that the use of information technology information and communication over the years has become one of the great allies for health professionals. Nursing has sought these tools to safely optimize the practice, which has enabled new paths based on a methodology for clinical practice. As a result, easier access to institutional protocols and content aggregation for care practices.